Exploring the Relationship Between Global Quality and Group Engagement in Toddler Child Care Classrooms. Issue 2 (3rd April 2017) - Hooper, Alison; Hallam, Rena
ABSTRACT: Toddlers' engagement with their social and physical environment is an important aspect of their experience in early care and education programs. The purpose of this research study was to examine how global quality relates to children's engagement in toddler child care classrooms. Additionally, this study explored how toddlers' group engagement levels vary across classroom contexts, including free play, group activities, meals, transitions, and personal care routines. Thirty toddler child care classrooms participating in a statewide Quality Rating and Improvement System (QRIS) were observed using two observational measures. Results indicate that a strong positive relationship exists between engagement and global quality. Group engagement varied significantly by classroom context, with the highest levels of engagement documented during mealtime and free play and the lowest levels of engagement documented during transitions. The findings point to the importance of using multiple measures to understand toddler experiences in group care settings. Further, the variation of children's engagement across classroom contexts suggests that more attention is needed in understanding and supporting teachers in increasing child engagement, especially during classroom transitions.